Effects of different frequencies of repetitive transcranial magnetic stimulation on sleep disorders and depression in patients with Parkinson’s disease: a systematic review and network meta-analysis - Xia, Yuan; Wan, Haili; Hu, Xin; Sun, Wenhui; Li, Yongjie (Frontiers in Aging Neuroscience, 2025)
BackgroundRepetitive transcranial magnetic stimulation (rTMS) has emerged as a promising neuromodulatory approach for alleviating sleep disturbances and depressive symptoms in Parkinson’s disease (PD), yet direct comparisons of different stimulation frequencies remain scarce.ObjectiveTo evaluate and rank the efficacy of three rTMS frequencies (1 Hz, 5 Hz, and 10 Hz), each combined with conventional therapy, on sleep disorders and depression in PD patients, thereby informing clinical decision-making.MethodsWe conducted a systematic search for randomized controlled trials (RCTs) in PubMed, Embase, the Cochrane Library, Web of Science, ProQuest, China National Knowledge Infrastructure, Wanfang, and the Chinese Scientific and Journal Database. A network meta-analysis was performed to compare the effects of different frequencies of rTMS (1 Hz, 5 Hz, and 10 Hz) on sleep disorders and depression in PD patients.ResultsThirty-one RCTs involving 1,977 PD patients met inclusion criteria. Compared with conventional treatment alone, adjunctive 5 Hz and 10 Hz rTMS produced significant improvements in both Pittsburgh Sleep Quality Index (PSQI) and Parkinson’s Disease Sleep Scale (PDSS). Although 1 Hz rTMS yielded numerically greater PSQI and PDSS improvements than conventional therapy, these differences did not reach statistical significance, nor did differences between the three stimulation frequencies. In terms of depressive symptoms, all three frequencies (1 Hz, 5 Hz, and 10 Hz) significantly reduced HAMD scores versus standard care, with head-to-head comparisons indicating superior efficacy of 10 Hz over 1 Hz and 5 Hz. The Surface Under the Cumulative Ranking area (SUCRA) consistently identified 10 Hz rTMS as the most effective frequency for PSQI, PDSS, and HAMD outcomes.ConclusionAdjunctive rTMS at 1 Hz, 5 Hz, and 10 Hz each confer benefits for sleep and mood in PD patients, but 10 Hz stimulation appears to offer the greatest overall improvement. These findings support the preferential use of 10 Hz rTMS when targeting non-motor symptoms in Parkinson’s disease.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/recorddashboard, identifier CRD42024614337.